Sistem Pembinaan Mental Spiritual Narapidana Wanita Di Lapas Kelas II. B Mojokerto Jawa Timur - Amru Almu'tasim (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2021)
Mental coaching is one way to shape human morals so that they have a moral, virtuous and moral personality, so that they can avoid reprehensible nature as a countermeasure against the emergence of criminal acts. Mental development is also the first foundation in Islamic teachings. A good mentality will give birth to good deeds and happiness in human life, both physically and mentally. (1) The stage of spiritual mental development of female prisoners at the Class IIB Mojokerto Penitentiary includes the admission stage, personality development stage, assimilation stage, and triangulation stage. (2) The material for the mental spiritual development of female prisoners at the Class IIB Mojokerto Penitentiary includes the values of aqidah, shari'ah values, and moral values. (3) Methods for developing the mental and spiritual mentality of female prisoners at the Class IIB Mojokerto Penitentiary include the interview method, group work method, enlightenment method, lecture method, demonstration method, and question and answer method. (4) The mental and spiritual development system for female prisoners at the Class II.B Mojokerto Penitentiary is carried out based on the principles of protection, service, education, guidance, respect.